1999
DOI: 10.1007/s002130051063
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral assessment of atypical antipsychotics in rats: studies of the effects of olanzapine (Zyprexa)

Abstract: On tests of jaw-movement activity and lever pressing after both acute and repeated drug administration, olanzapine demonstrated a profile somewhat similar to clozapine, and both of these drugs differ substantially from the typical antipsychotic haloperidol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 53 publications
3
13
1
Order By: Relevance
“…This finding is consistent with previous studies showing that cholinomimetic-induced tremulous jaw movements can be suppressed by other atypical antipsychotic drugs, including the prototypical compound clozapine (Stewart et al 1988;Chesler and Salamone 1996;Trevitt et al 1999) and the more recently developed drug olanzapine . As was the case with previous studies of clozapine and olanzapine (Trevitt et al 1997, quetiapine was also assessed for its ability to suppress lever pressing.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…This finding is consistent with previous studies showing that cholinomimetic-induced tremulous jaw movements can be suppressed by other atypical antipsychotic drugs, including the prototypical compound clozapine (Stewart et al 1988;Chesler and Salamone 1996;Trevitt et al 1999) and the more recently developed drug olanzapine . As was the case with previous studies of clozapine and olanzapine (Trevitt et al 1997, quetiapine was also assessed for its ability to suppress lever pressing.…”
Section: Discussionsupporting
confidence: 94%
“…Results from other typical and atypical antipsychotics also are shown. Behavioral data for additional drugs are from Trevitt et al 1997Trevitt et al , 1999Salamone et al 1998. Pimozide data are unpublished (Ishiwari et al 2005 work has shown that olanzapine and clozapine, like quetiapine, all have ED 50 ratios lower than 1.0, while the typical antipsychotics haloperidol and pimozide fail to suppress jaw movements, even at doses 3-11 times higher than the dose that suppresses lever pressing (Trevitt et al 1997Ishiwari et al 2005).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Moreover, the movement quality in these animals was jerky and irregular, not a regular tremor. We and others (Gunne et al, 1982;Ikeda et al, 1999;Tamminga et al, 1990;Trevitt et al, 1999) have argued for a connection between these VCMs and TD, and have suggested and tested a systems pathophysiology distinct from parkinsonism to account for the movements (Shirakawa and Tamminga, 1994;Sakai et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Olanzapine also seems to reduce anxiety and improve functioning of people with post-traumatic stress disorder (Petty et al 2001), Alzheimer's disease (Mintzer et al 2001), Huntington's disease (Squitieri et al 2001), or autism (Santosh and Baird 2001). Unlike typical antipsychotics, olanzapine's therapeutic effects occur with negligible extrapyramidal side effects and akathesia (Stanford and Fowler 1997;Steinpreis et al 1999;Trevitt et al 1999). Thus, olanzapine is a very useful drug.…”
Section: Introductionmentioning
confidence: 92%